THE SPLENDOR OF ALMERIA IN THE ELEVENTH CENTURY DURING THE PERIOD OF THE MULUK AL-TAWA’IF (KINGS OF TAIFAS) - Luisa Maria Arvide Cambra (European Scientific Journal, ESJ, 2015)
In this year 2014, is celebrated the Millennium of one of the most important periods in the history of Almeria, i.e. the Taifa Kingdom, in which an economic, social and cultural splendor was got, never before achieved. Three people were the main architects of this progress during the eleventh century in Almeria: Khayran, Zuhayr and Al-Mu‘tasim. This paper is an approach to the study of this glorious moment in the history of Almeria due to the achievements of these three relevant personages.